2012
DOI: 10.1016/j.neurobiolaging.2012.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal imaging pattern analysis (SPARE-CD index) detects early structural and functional changes before cognitive decline in healthy older adults

Abstract: This article investigates longitudinal imaging characteristics of early cognitive decline during normal aging, leveraging on high-dimensional imaging pattern classification methods for the development of early biomarkers of cognitive decline. By combining magnetic resonance imaging (MRI) and resting positron emission tomography (PET) cerebral blood flow (CBF) images, an individualized score is generated using high-dimensional pattern classification, which predicts subsequent cognitive decline in cognitively no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 60 publications
3
26
0
Order By: Relevance
“…Notably, we found that QA injections into mPFC actually increased FC strength between various cortical regions, which might in fact mimic the early, excitatory stages of Alzheimer-like neuropathology70. One of the advantages of the rsfMRI methodology is its ability to detect functional alterations that occur much earlier than structural changes377172. The reversal learning defects and spatial-cognitive rigidity, which we observed in our mPFC-lesioned mice, coincided with widespread changes in cortical connectivity.…”
Section: Discussionsupporting
confidence: 53%
“…Notably, we found that QA injections into mPFC actually increased FC strength between various cortical regions, which might in fact mimic the early, excitatory stages of Alzheimer-like neuropathology70. One of the advantages of the rsfMRI methodology is its ability to detect functional alterations that occur much earlier than structural changes377172. The reversal learning defects and spatial-cognitive rigidity, which we observed in our mPFC-lesioned mice, coincided with widespread changes in cortical connectivity.…”
Section: Discussionsupporting
confidence: 53%
“…Thus severity can be estimated by calculating the distance of each subject from the discriminating hyperplane. Such an approach has been been used in prior studies to quantify severity of the disorder, such as Alzhiemers’ and Mild Cognitive Impairment (Davatzikos et al, 2009; Clark et al, 2012) and Autism Spectrum Disorder (Ingalhalikar et al, 2011). Currently, MOE provides information about heterogeneity alone.…”
Section: Discussionmentioning
confidence: 99%
“…That is, what are the “normal” age effects on cognition? Previous work has clearly demonstrated that both brain atrophy and decline in neuropsychological test performance are key features of normal aging (Lamar et al, 2003; Resnick et al, 2003), and that the earliest observed changes are in structural and functional measures of the brain (Clark et al, 2012; Saykin et al, 2006). Yet, it is less clear whether such brain changes, and the previously highlighted fluid AD biomarker changes, fully explain age-related cognitive decline.…”
Section: Introductionmentioning
confidence: 99%